RESOLVING THE DATALESS DILEMMA IN OO PROGRAMMING. - Westfall, Ralph (Communications of the ACM, 2005)
Presents a letter to the editor focusing on the papers "Dataless Objects Considered Harmful" and "Hello, World Considered Harmful" that were published in the February 2001 and October 2001 issues of the periodical "Communications of the ACM" respectively.